Faktor Risiko Penularan Penyakit Skabies pada Santri di Pondok Pesantren An Nawawi Berjan Kecamatan Gebang Kabupaten Purworejo Jawa Tengah - Suci Ihtiaringtyas; Budi Mulyaningsih; Sitti Rahmah Umniyati (Balai Penelitian dan Pengembangan Kesehatan Banjarnegara Badan Litbangkes Kemenkes RI, 2019)
The high density of occupancy and poor environmental hygiene in An Nawawi Islamic Boarding School, Purworejo could effect on the health status of students. Scabies is one of health problem that often occurs in Islamic boarding schools. The aims of this study was to determine risk factors of scabies transmission on students at An Nawawi Boarding School Berjan Gebang subdistrict, Purworejo District of Central Java. This study used observational analytic methods using case-control design. The measured variables were environmental hygiene, residential density, personal hygiene, contact with patient, knowledge, sex, age and the presence or absence of house dust mites (TDR). The population in this study were students at Boarding School An Nawawi with the sample size is 104 students. Data obtained from environmental hygiene observational, questionnaires, physician diagnosis, skin swab sampling and sampling of house dust. Data were analyzed with Chi-Square (α=0.05). The result of this study showed that 115 of 161 students were diagnosed with scabies and S. scabiei was founded from 34 slide of skin swab. Environmental hygiene factors (p=0.000; OR=9.490), contact with patients (p=0.040; OR=2.912), sex (p=0.000; OR=5.083), and age of santri related to scabies transmission (p=0.000). House dust mites Dermatophagoides sp. found at An Nawawi Islamic Boarding School. Environmental cleanliness is the most dominant factor that influences the transmission of scabies at An Nawawi Islamic Boarding School